2017
DOI: 10.1080/23311908.2017.1389640
|View full text |Cite
|
Sign up to set email alerts
|

Application of the heuristic-systematic model to computer code trustworthiness: The influence of reputation and transparency

Abstract: Computer programs (code) are integral to the functions of current society. Yet, little is known about why programmers trust code they did not create. The current paper applied the heuristic-systematic model (HSM) of information processing to perceptions of code trust for reuse. The studies explored transparency (readability and organization) and reputation (source) as factors that influenced trust perceptions and time spent reviewing code using professional programmers. Source and readability manipulations led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 35 publications
(54 reference statements)
4
32
1
Order By: Relevance
“…The source of the repairs had a significant influence on all variables assessed in the current study. This is not surprising as previous research in both computer science and psychology [14,16,20] has demonstrated the source of the code (i.e., reputation) as an important factor that influences reuse and trust perceptions in code. The current study also supports the hypotheses of Madhavan and Weigmann [23] that humans hold biases in perceptions against automation when they perceive they can perform the task themselves, as participants consistently rated GenProg lower than a human.…”
Section: Sourcementioning
confidence: 71%
See 4 more Smart Citations
“…The source of the repairs had a significant influence on all variables assessed in the current study. This is not surprising as previous research in both computer science and psychology [14,16,20] has demonstrated the source of the code (i.e., reputation) as an important factor that influences reuse and trust perceptions in code. The current study also supports the hypotheses of Madhavan and Weigmann [23] that humans hold biases in perceptions against automation when they perceive they can perform the task themselves, as participants consistently rated GenProg lower than a human.…”
Section: Sourcementioning
confidence: 71%
“…Several experimental findings have highlighted the utility of the HSM in the context of trustworthiness of computer code. Alarcon and colleagues [16], for example, found that properties of code (e.g., readability and source of the code) served as cues programmers used to inform their trust toward the code. Specifically, when readability and perceived source were degraded, trust levels declined and human processing speed was shortened, despite that the code compiled successfully and was free from performance errors.…”
Section: Trust In Codementioning
confidence: 99%
See 3 more Smart Citations